El consumo sustentable: un principio implícito en el sistema chileno de consumo - Isler Soto, Erika (2024)
The Chilean Consumer Protection Law does not mention sustainable consumption as an explicit principle. In this context, the objective of this work lies in investigating its possible validity as a general principle of consumer law in Chile. The research managed to prove the initial hypothesis that postulated the legal effectiveness of sustainable consumption as a general principle of consumer law. In fact, from the use of the dogmatic methodology, it was concluded that its validity can also be derived from a harmonious and systematic interpretation of the principles and rules that the Chilean legal system actually contains. Specifically, the normative effectiveness of sustainable consumption can be derived from two ways within the techniques of legal positivism. The first of them consists of a concretization of general principles, which, in the hypothesis presented, would correspond to pro natura and pro homine. Secondly, sustainable consumption as a general principle would be obtained from a generalization made from specific manifestations. The latter would be rooted in the consecration of basic consumer rights, the discipline of information and advertising, as well as the establishment of mechanisms to extend the durability of goods.